STUDI FENEMONOLEGI: STRATEGI KOPING ORANG TUA DALAM MERAWAT ANAK AUTISM SPECTRUM DISORDER (ASD) - Hidayah, Ridhoyanti; Yusuf, Ahmad; Fitryasari, Rizky (Jurnal Keperawatan, 2017)
STUDI FENEMONOLEGI: STRATEGI KOPING ORANG TUA DALAM MERAWAT ANAK AUTISM SPECTRUM DISORDER (ASD) Coping Strategy Used by Parents of Children with Autism Spectrum Disorder (ASD)  Ridhoyanti Hidayah1, Ah.Yusuf2, Rizky Fitryasari31Jurusan Keperawatan Fakultas Kedokteran Universitas Brawijaya2,3Program Magister Prodi Keperawatan Fakultas Keperawatan Universitas AirlanggaEmail: 1)ridhoyanti.fk@ub.ac.id ABSTRACTCoping strategies are important predictors of psychosocial adaptation among parents of children with ASD. This study aimed to explore coping strategies used by parents of children with ASD. This descriptive phenomenology study used in-depth semi-structured interviews to explore parents experiences. Six participants were recruited from Pusat Layanan Autis Kota Malang by using purposive sampling. The interviews were digitally recorded and transcribed verbatim. The thematic were analyzed using Colaizi’s phenomenological method. Eight themes were extracted according to the spesific purposes: (1) caring demand; (2) social stigma; (3) level of ASD severity; (4) life stressor of parent as a caregiver; (5) constructive coping strategies: seeking for information, formal support, spiritual approach, relaxation, and positif thinking (6) destructive coping strategies: physical and verbale action; (7) positive life meaning: change of the way of thinking and behavior, and (8) negative life meaning: stress feeling of having ASD children. It can be concluded that both constructive and destructive coping strategies were used by parents when dealing with children with ASD. Futher investigation with parents living in rural areas is needed to explore their constructive coping strategies using phenomenology study design.Key words: coping strategies, parents, autism spectrum disorder